EFEKTIVITAS PELAYANAN PRIMA BAGIAN POLI PADA PUSKESMAS PONDOK AREN TANGERANG - Agus Tri Indah K; Harun Al Rasyid; Dirgahayu Erri (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
Excellent service is caring for customers by providing the best service to facilitate the convenience of customer needs. Excellent service plays an important role in an organization and can provide a positive image for the organization. Puskesmas is a government-owned organization, the service at the Puskesmas will affect population loyalty to the Government. Although many customers (patients) will not reduce the income (salary) of employees. The study was conducted using qualitative descriptive method data obtained based on the results of observations and interviews. The strategic location of the Pondok Aren Community Health Center, located in a residential area and surrounded by people with a very dense middle and lower income is a very strategic potential for treatment at the Community Health Center. Services at the Pondok Aren Health Center are quite effective, this can be seen from the running of the program outside the building and inside the building to provide strategic services in order to improve public health. Examination in the poly section provides the best service with a number of poly which includes diseases in general, teeth, children and even the elderly. The amount of poly available is sufficient so that there is no accumulation of patients in the waiting room. With this good service, puskesmas have a very wide opportunity or potential to develop in the Pondok Aren and surrounding areas.